Students Perceptions on Simulation as Part of Experiential Learning in Approaches, Methods, and Techniques (AMT) Course - Purnomo, Marselina Karina (LLT Journal: A Journal on Language and Language Teaching, 2017)
Simulation is a part of Experiential Learning which represents certain real-life events. In this study, simulation is used as a learning activity in Approaches, Methods, and Techniques (AMT) course which is one of the courses in English Language Education Study Program (ELESP) of Sanata Dharma University. Since simulation represents the real-life events, it encourages students to apply the approaches, methods, and techniques being studied based on the real-life classroom. Several experts state that students are able to involve their personal experiences through simulation which additionally is believed to create a meaningful learning in the class. This study aimed to discover ELESP students perceptions toward simulation as a part of Experiential Learning in AMT course. From the findings, it could be inferred that students agreed that simulation in class was important for students learning for it formed a meaningful learning in class.